Effect of using Agrogeotextiles on soil carbon sequestration in the Indian Himalayas - ROY, PLABANI; BHATTACHARYYA, RANJAN; BISWAS, D R; SINGH, RAMANJEET; DAS, T K; SHARMA, D K; YADAV, SUNITA; JOSEPH, ANN MARIA; JHA, PRAMOD (The Indian Journal of Agricultural Sciences, 2023)
Agrogeotextiles (AGT) have potential for soil conservation, but limited information is available on effect of AGT on C sequestration and soil aggregation in Indian Himalayan region (IHR). Hence, the study was conducted on a 4% slope at Selakui, Dehradun in a maize-based cropping system where Arundo donax mats were used as AGT mats for soil conservation. Soil sampling was done in December 2021 after vegetable pea harvest and results indicated that in 0–15 cm soil depth, Maize + Arundo donax mat (10 cm thick) on 0.5 m vertical interval vegetable pea - wheat (M+A10D0.5-V-W) had 23% higher total soil organic C (TSOC) in bulk soils than the control (M-W) plots. Plots with Arundo donax mats exhibited 12% higher TSOC than plots without the mats. Plots under M+A10D0.5-V-W and maize-vegetable pea-wheat under bench terracing (M-V-W)B showed similar impacts on C sequestration. M+A10D0.5-V-W plots had 36% greater macroaggregate and 35% higher mean weight diameter (MWD) than M-W plots in the 0–15 cm soil depth. Microbial biomass C (MBC) enhanced by 86% under M+A10D0.5-V-W over M-W in the 0–15 cm soil depth due to higher root biomass, root exudates and metabolizable C. Thus, microbial quotient (MQ) was also increased. Mean annual soil loss value of 2020–2021 and 2021–2022 ranged from 0.4 t/ha/yr to 2.9 t/ha/yr which was correlated with carbon management index (CMI) value. The CMI was 38% higher in M+A10D0.5-V-W plots than M-W due to emplacement of Arundo donax mats, resulting in better soil aggregate stability. Thus, AGT application can be a potential practice for soil aggregation stability and C sequestration in the IHR. Conservation soil practices along with AGT are more profitable than conservation soil practices alone which had 10% less benefit : cost ratio (B:C) on 4% land slopes of IHR.